IoT Trainer Kit Training For Vocational School Teachers As Preparation Towards The 4.0 Industry Era - Rahayu, Maya; Hariyanto, Teddi; Fadhlan, M. Yusuf (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2020)
In welcoming industry 4.0, teachers in vocational education are required to be able to make students be ready to enter the industry. However, the ability of vocational teachers to replace industry 4.0 is not optimal yet. One of the reason is unavailability of learning media to support IoT-based learning. We use an IoT training kit to make teachers easier to understand the Internet of Things. This trainer kit is equipped with an Arduino, some input devices and communication devices. These features are expected to improve teacher understanding of IoT, making it easier to implement it in the teaching-learning process with their students. The methodology used in this journal is quantitative research, with experimental research designs. The type of experiment used is the type of pre-experimental design, in the form of one group pre-test-post-test. The results of this training can improve the learning outcomes from the cognitive realm is 31.45%.